Kearifan Lokal: Fenomena Pengobatan Supranatural dalam Perspektif Kemashalatan - Firja Endriza; Muhammad Habibi Siregar (Syntax Corporation, 2023)
The phenomenon of relatively expensive health services that cannot be afforded by everyone, especially those with a low standard of living, has caused some people to choose alternative medical routes that are easier and more cost-effective. This study aims to find out the reasons why people still use supernatural healing. The research method is to use a research method through a qualitative descriptive method in which the author conducts interviews and analyzes any developments related to these problems. The results of this study indicate that people's perceptions of supernatural healing originate from a form of belief in the strange diseases they experience. There are several factors that become reasons for doing supernatural healing, namely; medical expenses, personal experience, simple methods and fast recovery.